Assessing the efficacy of various treatment regimens for patients with endocrine ophthalmopathy associated with Graves' disease - Yu. V. Buldygina; G. M. Terekhova; L. S. Strafun; I. I. Savosko; Z. G. Lysova; S. L. Shlyakhtych (Ukrainian Society of Ophthalmologists, 2022)
Purpose: To assess the efficacy of various treatment regimens for patients with EO associated with Graves' disease based on the retrospective analysis of clinical data, thyroid-stimulating hormone (TSH) receptor autoantibodies (TSHR-Ab) titers and orbital ultrasound imaging findings. Material and Methods: We retrospectively reviewed the medical records (including clinical and laboratory data and findings of ultrasound imaging of retrobulbar adipose tissue) of 155 patients with EO associated with Graves' disease and either euthyroidism (in the presence of antithyroid therapy) or postoperative compensated hypothyroidism that underwent treatment at Komisarenko Institute for Endocrinology and Metabolism between 2009 and 2019. The duration of EO ranged from 8 months to 36 months. Patients with EO associated with Graves' disease were medically treated in the presence of stable euthyroidism. Patients were divided into 4 groups based on the glucocorticoid treatment scheme. Group 1 of 15 patients received prednisolone tablets per os; group 2 of 68 patients, intravenous methylprednisolone (MP) pulse therapy only; group 3 of 32 patients, intravenous MP pulse therapy plus vitamin D3; and group 4 of 40 patients, intravenous MP pulse therapy 8 to 12 months after thyroidectomy. Results: As soon as 3 months after treatment initiation, there was an improvement in condition of patients in all groups as assessed by clinical examination, followed by further improvement by 6 months and 12 months. The best results were obtained in patients of group 4, with a statistically significant improvement in clinical condition (p < 0.05). Retrobulbar adipose tissue thickness as assessed by orbital ultrasound at baseline and at 6 months and 12 months was statistically significantly greater in patients of all the four groups than controls (p < 0.05). At 6 months, serum TSHR-Ab levels in groups 1, 2 and 3 significantly decreased compared to baseline, with no significant difference between these groups, whereas serum TSHR-Ab level in group 4 was significantly higher than in other groups both at baseline and at 6 months. At 12 months, serum TSHR-Ab level in group 4 was significantly lower (р < 0.05) than in other groups (2.41 ± 0.81 mU/L versus 5.97 ± 1.71 mU/L for group 1, 5.49 ± 1.27 mU/L for group 2, and 6.17 ± 1.18 mU/L for group 3). Conclusion: Patients with EO associated with Graves' disease in group 4 (intravenous MP pulse therapy after thyroidectomy) showed a significantly better (р < 0.05) treatment outcome than patients in other groups. Ultrasound imaging of retrobulbar adipose tissue thickness is inadequately informative for assessing treatment efficacy.